2022
DOI: 10.3390/ijerph19159037
|View full text |Cite
|
Sign up to set email alerts
|

Chinese Residents’ Healthy Eating Intentions and Behaviors: Based on an Extended Health Belief Model

Abstract: Unhealthy eating is one cause of obesity and some chronic non-communicable diseases. This study introduces self-efficacy and health consciousness to construct an extended health belief model (HBM) to examine the factors influencing healthy eating intentions and behaviors of Chinese residents and explore the moderating effect of perceived barriers and the mediating effect of healthy eating intentions. Through the survey platform “Questionnaire Star”, this study collected quantitative data from 1281 adults, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 55 publications
(51 reference statements)
0
4
0
Order By: Relevance
“…Barriers of accessibility, mobility, and dependence on others for meals have previously been voiced by individuals with SCI/D, their informal caregivers, and SCI healthcare providers (LaVela, Pellegrini, et al, 2022). Y. Wang et al (2022) found that perceived barriers to healthy eating were associated with negative healthy eating intentions and behaviors in a non-SCI/D population.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Barriers of accessibility, mobility, and dependence on others for meals have previously been voiced by individuals with SCI/D, their informal caregivers, and SCI healthcare providers (LaVela, Pellegrini, et al, 2022). Y. Wang et al (2022) found that perceived barriers to healthy eating were associated with negative healthy eating intentions and behaviors in a non-SCI/D population.…”
Section: Discussionmentioning
confidence: 94%
“…Y. Wang et al (2022) found that perceived barriers to healthy eating were associated with negative healthy eating intentions and behaviors in a non-SCI/D population. In the current study, participants specifically discussed challenges to independently grocery shopping (e.g., difficulty getting to stores, transportation, and navigating aisles), preparing (e.g., unable to chop vegetables), and similar to findings by Holla et al (2020) barriers to cooking (e.g., unable to reach standard stovetop) for oneself often leading to consumption of processed, microwavable/instant foods, fast foods for convenience, or relying on others for meals.…”
Section: Discussionmentioning
confidence: 99%
“…When the main effect is significant, if the lower limit and upper limit contain 0, the mediation effect does not exist. If 0 is not included, there is a mediation effect [ 71 , 72 ]. In AMOS, We set the sample size at 5000 with 95% confidence.…”
Section: Resultsmentioning
confidence: 99%
“…The usual solution to cover the gap or to improve the behavioral findings is to consider adding more components, variables, or constructs to the TPB [ 62 , 63 , 64 ]. On the other hand, the HBM provides a more thorough analysis of health-related attitudes and actions [ 65 ]. This has been used to assess perception and belief among individuals when dealing with studies related to health [ 27 , 28 , 29 ].…”
Section: Conceptual Frameworkmentioning
confidence: 99%